Flip This Classroom: A Comparative Study. Issue 1 (2nd January 2016) - Unruh, Tiffany; Peters, Michelle L.; Willis, Jana
Abstract: The purpose of this research was to compare the beliefs and attitudes of teachers using the flipped versus the traditional class model. Survey and interview data were collected from a matched sample of in-service teachers representing both models from a large suburban southeastern Texas school district. The Attitude Towards Technology Scale, the Frequency of Involvement in Technology Scale, the Technology Comfort Scale, and the Technology and Teaching Efficacy Scale were administered to compare the beliefs and attitudes of teachers. Additionally, one-on-one interviews further explored the teacher beliefs and attitudes associated with the impact of technology on student engagement. Findings suggest that flipped classroom teachers have higher technology and teaching efficacy, greater comfort levels using technology, higher frequency of involvement in technology, more positive attitudes toward technology, and greater levels of student engagement.